SOCIAL COMPOSITION OF BABUR’S STATE IN INDIA (TAMADDUN NURI JURNALI, 2024)
Zakhiriddin Muhammad Babur, a descendant of the Timurids, known as a poet, writer, historian, commander, head of state, founded the Mughal Empire in India, which lasted 300 years. During the reign of Babur and his descendants, the social structure of the state was complex and had a large number of different classes.